PERAN GURU AGAMA ISLAM DALAM UPAYA MEWUJUDKAN SEKOLAH RAMAH ANAK DI SMAN 29 JAKARTA SELATAN (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the role of Islamic Religious Education (PAI) teachers in implementing Child-Friendly Schools (CFS) at SMA Negeri 29 Jakarta Selatan. The research employs a qualitative case study design with data collectet through interviews,observations,and documentation, which are analyzed using triangulation techniques.The findings indicate that PAI teachers have a comprehensive understanding of CFS by integrating Islamic spiritual values with principles of inclusivity and child protection.The implementation is reflected in strategies for handling disciplinary issues and bullying through preventive and educative approaches,supported by the Violence Prevention and HandlingTeam (TPPK) and adaptive school regulations.In addition,teachers create a safe and inclusive learning environment through contextual learning,varied teaching methods, dialogical interaction,and differentiated instruction.The internalization of tolerance and diversity values is carried out through interfaith activities and active student participation.Supporting factors include pro-child schoo policies,active teacher involvement,and collaborationvwith parents andbthe community.However, challenges remain, such as inconsistent understanding of CFS among educators, limited human resources and budget,and adolescent behavioral issues .Overall, the implementatio of CFS has been carried out systematically and sustainably, although continuous improvement is still needed.This study emphasizes the importance of the teacher’s role as a key agent in realizing a humane and inclusive educational environment.